TI1e Influence of TrailS Europe Lines Project on Telecommunications Development - Brlić, Vladimir; Žurić-Hudel, Vlasta (Promet - Traffic&Transportation)
A multinational Project Trans Europe Lines (TEL) is ofgreat importance for the present development as well as for thefuture role and situation of telecommunications in the cowl·tries of Central and Eastern Europe (CEE). The idea of the necessityof constructing a fibre optic (FO) telecommunicationb1idge between Eastem and Westem Europe was initiated bythe Deutsche Bundespost Telekom and presented to some ofthe telecommunication administrations in that region in theyear 1990. The basic aim of the Project is to enable all countliesto improve and satisfY the telecommunication needs on internationaland national levels, to ensure sufficient transmissiontelecommunication infrastrncture in intemational traffic, toenable establishing of intense economic interrelations, to providethe basis for the development of future telecommunicationservices, and to support complete economic development in theCEE region.After its initialisation, the TEL Project was graduallyjoined by new Members and by the end of 1996 it included 16countries. Since initialisation until the end of 1996 TEL almosttripled in size regarding the physical area covered, and it becametwice as big regarding the involved number of inhabitants(potential subscribers).VarimLSt reasons were the ’driving force’ for the numerouscountries insufficiently developed in the field of telecommunicationsand involved in the Project (as, for example, for the Republicof Croatia, in which TEL strongly supported its telecommunicationsdevelopment in spite of the difficulties of the warperiod 1991-1995 in the country).Thanks to the FO cable transmission systems which havebeen or are still being built within the framework of the TELProject and which represent the infrastntcture for the true CEEinformation highway, in the field of telecommunications, theProject M embers are not only connected among themselves butalso with the whole world, since the direct access points to TELare at locations of numerous ’landing points’ of the intemationalFO submarine cables.